Next Generation 2008 a Selection of Short Films by Students of German Film Schools - Bilgeri, Tobias; Sehr, Markus; Herzog, Lothar (German Films Service, 2008)
In recent years, German films have been able to celebrate remarkable international successes: frequent accolades like the Academy Award and the European Film Prize provide evidence of this, as well as flourishing overseas sales and some excellent audience figures. There comes a time, in face of such positive development, when one asks quite justifiably: will these successful filmmakers turn out to be a single "golden" generation, or will the measures to promote up-and-coming filmmakers take effect on a longer-term basis, and this success even continue to motivate students in our film schools, releasing creative impulses there? The short-film programm "Next Generation 2008" offers answers to such speculation by taking a bold look - as a cross-section of German film academy work - at the heart of our cinematic future. [Beiheft]